Primate liver tissue substrate in indirect immunofluorescence diagnostics for patients with dermatitis herpetiformis and celiac disease - Schauer, Franziska; Tasiopoulou, Georgia; Schuster, Daniel; Behrens, Max; Müller, Sabine; Kiritsi, Dimitra (Frontiers in Immunology, 2023)
Introduction Dermatitis herpetiformis (DH) is a rare autoimmune, polymorphous blistering disorder, characterized by severe itch or burning sensation, which represents the cutaneous manifestation of celiac disease (CD). The current estimation of DH versus CD is around 1:8 and the affected individuals have a genetic predisposition. Pathogenetically, IgA autoantibodies against the epidermal transglutaminase, an essential constituent of the epidermis, cause DH and are reported to develop through cross-reaction with the tissue transglutaminase, with IgA auto-antibodies causing CD. Immunofluorescence techniques allow for a rapid diagnostics of the disease using patient sera. Evaluation of IgA endomysial deposition with indirect immunofluorescence on monkey oesophagus is highly specific, but moderately sensitive, with some operator-dependent variability. Recently, indirect immunofluorescence with monkey liver as a substrate has been proposed as an alternative, well-functioning diagnostic approach with higher sensitivity in CD. Methods The objective of our study was to evaluate whether monkey oesophagus or liver tissue shows advantage for diagnostics in patients with DH, compared to CD. To that end, sera of 103 patients with DH (n=16), CD (n=67) and 20 controls ere compared by 4 blinded experienced raters. Results For DH, we found a sensitivity of 94.2% for monkey liver (ML) compared to 96.2% in monkey oesophagus (ME), while specificity in ML was superior (91.6% versus 75%) to ME. In CD, ML had a sensitivity of 76.9% (ME 89.1%) and specificity of 98.3% (ME 94.1%). Discussion Our data show that ML substrate is well suitable for DH diagnostics.